Interpenetrating network phase change fiber and preparation method thereof

By encapsulating the phase change material in a porous structure shell, and using ultrasonic dispersion and freeze-drying technology to prepare phase change nano microspheres, combined with wet spinning technology to form phase change fibers with interpenetrating network structures, the existing phase change is solved The problem of insufficient heat resistance and stability of fibers significantly improves its enthalpy and thermal stability properties.

CN118186613BActive Publication Date: 2025-02-14WUHAN INSTITUTES OF ADVANCED TECHNOLOGY CHINESE ACADEMY OF SCIENCES
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410333301.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-22
Publication Date
2025-02-14
Estimated Expiration
2044-03-22

AI Technical Summary

Technical Problem

The existing phase change fibers lack heat resistance and stability during the hot and cold cycle, resulting in a decrease in the enthalpy of phase change, affecting their application performance.

Method used

By encapsulating the phase change material in a shell material with a porous structure, phase change nano microspheres are prepared by ultrasonic dispersion and freeze-drying technology, and combined with a wet spinning process, phase change fibers with interpenetrating network structure are formed.

Benefits of technology

It improves the enthalpy and thermal stability properties of phase change fibers, and enhances its application value in the fields of human body insulation, medical care and construction.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118186613B_ABST
    Figure CN118186613B_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of phase change materials, and in particular to an interpenetrating network phase change fiber and a preparation method thereof. The preparation method of the interpenetrating network phase change fiber provided in the present application comprises the following steps: ultrasonically dispersing the phase change material, monomer, initiator and stabilizer, heating the reaction, stirring, and obtaining a mixed solution; freeze-drying the mixed solution to obtain phase change nano-microspheres, adding water, and obtaining a phase change nano-microsphere suspension; dissolving the wet spinning raw material in a solvent to obtain a spinning solution, and preparing wet spinning fibers using a wet spinning process; immersing the wet spinning fibers in the phase change nano-microsphere suspension in a vacuum environment, and after the immersion is completed, washing and drying to obtain an interpenetrating network phase change fiber. The present application encapsulates the phase change material in a shell material with a porous structure. This structure can improve the heat resistance and stability of the material, and can be used in phase change fibers to increase their phase change enthalpy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of phase change materials, and in particular to an interpenetrating network phase change fiber and a preparation method thereof. Background Art

[0002] Phase change thermoregulating fiber is a smart fiber with temperature regulating function. It can absorb or release heat through the phase change process of the material. Phase change thermoregulating fiber uses the property of phase change material to change its physical state at a specific temperature to absorb or release heat. When the ambient temperature rises, the phase change material changes from solid to liquid and absorbs heat; when the ambient temperature drops, the phase change material changes from liquid back to solid and releases heat, thereby achieving the effect of regulating temperature. This fiber is widely used in the production of functional clothing, such as sportswear, ski equipment and space suits, to maintain a comfortable temperature for the wearer.

[0003] Phase change fiber essentially achieves temperature control performance through phase change materials such as microcapsules. For example, patent CN116751566A discloses a composite phase change material for phase change temperature control fiber and its preparation method. Silicon dioxide nanospheres are selected as porous carriers and phase change medium polyethylene glycol in the preparation process to form physical adsorption without any chemical reaction. After 100 hot and cold cycles, the phase change temperature and enthalpy value have not changed significantly, and the structure is stable. However, alkaline catalysts are added during the preparation process, and the reaction controllability is poor. Patent CN116555937A discloses a preparation method for composite phase change fiber. No matter how the filler content changes, this fiber does not agglomerate, has good dispersibility, and has no significant change in phase change temperature and enthalpy value after 50 hot and cold cycles. However, the required preparation process steps are cumbersome and difficult to control. Patent CN116590915A discloses a photo-induced heating and temperature-sensitive elastic phase-change energy storage fiber and its preparation method. The thermal conductive material is evenly dispersed in the phase-change material, which is loaded into a porous elastic polyurethane fiber after vacuum drying. A protective layer is then coated on the fiber surface to obtain the corresponding phase-change fiber. This phase-change fiber has a three-dimensional porous network structure, and the internal and external pore structures are connected, but its pore size is relatively large, most of which are above 50μm.

[0004] Based on the above analysis, it is very important to provide a phase change fiber that can improve the heat resistance and stability of the material. Summary of the invention

[0005] An embodiment of the present application provides a method for preparing an interpenetrating network phase change fiber. The present application encapsulates a phase change material in a shell material with a porous structure. This structure can improve the heat resistance and stability of the material and is used in the phase change fiber, thereby increasing its phase change enthalpy value.

[0006] In a first aspect, the present application provides a method for preparing an interpenetrating network phase change fiber, comprising the following steps:

[0007] S101, ultrasonically dispersing the phase change material, monomer, initiator and stabilizer, heating for reaction and stirring to obtain a mixed solution;

[0008] S102, freeze-drying the mixed solution to obtain phase-change nano-microspheres, adding water to obtain a phase-change nano-microsphere suspension for later use;

[0009] S103, dissolving a wet spinning raw material in a solvent to obtain a spinning solution, and preparing a wet spinning fiber by a wet spinning process;

[0010] S104, impregnating the wet-spun fiber in a phase change nano-microsphere suspension in a vacuum environment, washing and drying at room temperature of 25° C., thereby obtaining an interpenetrating network phase change fiber.

[0011] In some embodiments, in step S101, the weight proportions of the raw materials are: 30-100 parts of phase change material, 0.2-1 parts of initiator, 0.5-2 parts of stabilizer, and 5-20 parts of monomer.

[0012] In some embodiments, the phase change material is a mixture of any one or more of polyethylene glycol, paraffin, and high-density polyethylene.

[0013] In some embodiments, the monomer is selected from any one of methyl methacrylate, styrene, and polydimethylsiloxane. Under the action of the initiator, the monomer is polymerized to form the shell material of the phase-change nano-microspheres.

[0014] In some embodiments, the initiator is selected from any one of styrene-maleic anhydride hydrolyzate, potassium persulfate, and dibenzoyl peroxide.

[0015] In some embodiments, the stabilizer is selected from a mixture of any one or more of an organic tin stabilizer, a lead stabilizer, and a rare earth stabilizer. The stabilizer is used to adjust the pH of the reaction system and promote the reaction.

[0016] In some embodiments, the organic tin stabilizer is a mixture of any one or more of dibutyltin dimaleate, dibutyltin dilaurate, butyltin sulfate, etc.; the lead stabilizer is a mixture of any one or more of dibasic lead stearate, dibasic lead salt, dibasic lead phthalate, etc.

[0017] In some embodiments, the wet spinning raw material is a mixture of any one or more of polyurethane, chitosan, and cellulose.

[0018] In some embodiments, the freeze-drying process has a freezing temperature of -20 to -200°C, a freezing time of 30 to 60 minutes, a drying time of 6 to 12 hours, and a vacuum condition of 2-5 Pa.

[0019] In some embodiments, in step S101, the heating temperature is 50-80°C, and the stirring speed is 3000-5000 rpm.

[0020] In some embodiments, in step S103, the concentration of the spinning solution is 20-60 wt %, and the flow rate is 0.1-50 m / min.

[0021] In some embodiments, in step S104, the immersion temperature is 50-150° C., and the immersion time is 1-4 hours.

[0022] In a second aspect, the present application also provides an interpenetrating network phase change fiber prepared by the above preparation method.

[0023] The beneficial effects of the technical solution provided by this application include:

[0024] The present application prepares nano-microspheres with a core material of phase change material and a shell material of porous structure by adding a mixture of initiator, stabilizer and monomer into a phase change material, using high-speed stirring during the preparation process, and finally freeze-drying, wherein the macromolecular chains of the core material and the shell material of the nano-microspheres are interlaced and cross-linked to form an interpenetrating network structure; the nano-microspheres are formed by irregular accumulation of countless small spheres with a particle size of about 200 nm, and when the wet-spun fibers are immersed in a phase change nano-microsphere suspension, the phase change nano-microspheres are dispersed in the solution and released into the fibers, and since there are pore structures between the fibers, the phase change nano-microspheres will be free in the pores during the immersion process to form a load; the present application applies phase change nano-microspheres to wet spinning to prepare phase change fibers, which effectively improves the enthalpy value and thermal stability of the phase change fibers, and has extremely high commercial value and application prospects in the fields of human body insulation, medical treatment and construction. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0026] Figure 1 This is a SEM electron microscope image of the phase change nanospheres prepared in Example 1 of the present application.

[0027] Figure 2 This is a DSC curve diagram of the phase change fiber prepared in Example 1 of the present application.

[0028] Figure 3 This is a DSC curve diagram of the phase change fiber prepared in Example 2 of the present application.

[0029] Figure 4 This is the DSC curve of the phase change fiber prepared in Comparative Example 1. DETAILED DESCRIPTION

[0030] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0031] The present invention provides a method for preparing an interpenetrating network phase change fiber, comprising the following steps:

[0032] Step S101, by weight, 30-100 parts of phase change material, 0.2-1 parts of initiator, 5-20 parts of monomer and 0.5-2 parts of stabilizer are ultrasonically dispersed, heated at 50-80° C. for reaction, and stirred to obtain a mixed solution;

[0033] Step S102, freeze-drying the mixed solution to obtain phase-change nano-microspheres, adding water to obtain a phase-change nano-microsphere suspension with a mass concentration of 20%-30%, for standby use; the freezing temperature of freeze-drying is -20 to -200°C, the freezing time is 30 to 60 minutes, the drying time is 6 to 12 hours, and the vacuum condition is 2-5 Pa;

[0034] S103, dissolving a wet spinning raw material in a solvent to obtain a spinning solution, and preparing a wet spinning fiber by a wet spinning process;

[0035] S104, the wet-spun fibers are subjected to vacuum treatment to remove the contained air and moisture, and then the treated wet-spun fibers are placed in an impregnation container, vacuumized, and a phase change nano-microsphere suspension is added to impregnate the wet-spun fibers at 50-150° C. After impregnation for 1-4 hours, the fibers are washed and dried at room temperature at 25° C. to obtain an interpenetrating network phase change fiber.

[0036] Among them, the phase change material is a mixture of any one or more of polyethylene glycol, paraffin, and high-density polyethylene; the monomer is any one of methyl methacrylate, styrene, and polydimethylsiloxane; the initiator is any one of styrene-maleic anhydride hydrolyzate, potassium persulfate, and dibenzoyl peroxide; the stabilizer is a mixture of any one or more of organic tin stabilizers, lead stabilizers, and rare earth stabilizers; the organic tin stabilizer is a mixture of any one or more of dibutyltin dimaleate, dibutyltin dilaurate, butyltin sulfate, etc.; the wet spinning raw material is a mixture of any one or more of polyurethane, chitosan, and cellulose.

[0037] The interpenetrating network phase change fiber and the preparation method thereof provided by the present application are described in detail below in combination with embodiments and comparative examples.

[0038] Embodiment 1:

[0039] (1) Weigh 40 g of polyethylene glycol, 1 g of styrene-maleic anhydride hydrolyzate, 6 g of methyl methacrylate, and 1 g of dibutyltin dimaleate, dissolve them in water, and after ultrasonic dispersion for 10 min, place them in an oil bath and heat them to 50° C. for reaction for 1 h; start a high-speed stirrer, adjust the stirring rate to 5000 rpm, increase the reaction temperature to 80° C., and react for 6 h to obtain a mixed solution;

[0040] (2) After the mixed solution is taken out and cooled, it is placed in a freeze dryer, frozen for 30 minutes at a vacuum degree of 5 Pa and a temperature of -50°C, and dried for 12 hours to obtain phase change nanoparticles, and water is added to prepare a phase change nanoparticle suspension with a mass concentration of 30% for later use;

[0041] (3) dissolving polyurethane in anhydrous ethanol to obtain a spinning solution with a concentration of 40 wt%, using pure water as a coagulation bath, wet spinning at room temperature, with a flow rate set at 1 m / min, and obtaining wet-spun fibers after curing for 30 min;

[0042] (4) The wet-spun fibers are subjected to vacuum treatment to remove the air and moisture contained therein, and then the treated wet-spun fibers are placed in an impregnation container, vacuumized, and a phase change nanosphere suspension is added to impregnate the wet-spun fibers at 50° C. After impregnation for 4 hours, the fibers are washed and dried at room temperature at 25° C. to obtain phase change fibers.

[0043] The SEM electron microscope image of the phase change nanospheres prepared in Example 1 is shown in Figure 1 ,from Figure 1 It can be seen that the shell material of the phase change nanospheres has a porous structure.

[0044] The DSC curve of the phase change fiber obtained in Example 1 is shown in Figure 2 .

[0045] Embodiment 2:

[0046] (1) Weigh 35 g of paraffin wax, 0.5 g of styrene-maleic anhydride hydrolyzate, 8 g of styrene, and 0.6 g of butyltin sulfate, dissolve them in water, and after ultrasonic dispersion for 15 min, place them in an oil bath and heat them to 50° C. for reaction for 1 h; start a high-speed stirrer, adjust the stirring rate to 4000 rpm, increase the reaction temperature to 80° C., and react for 6 h to obtain a mixed solution;

[0047] (2) After the mixed solution is taken out and cooled, it is placed in a freeze dryer, frozen for 30 minutes at a vacuum degree of 3 Pa and a temperature of -40°C, and dried for 12 hours to obtain phase change nanoparticles, and water is added to prepare a phase change nanoparticle suspension with a mass concentration of 25% for later use;

[0048] (3) dissolving polyurethane in anhydrous ethanol to obtain a spinning solution with a concentration of 35 wt%, using pure water as a coagulation bath, wet spinning at room temperature, with a flow rate set at 2 m / min, and obtaining wet-spun fibers after curing for 30 min;

[0049] (4) The wet-spun fibers are subjected to vacuum treatment to remove the air and moisture contained therein, and then the treated wet-spun fibers are placed in an impregnation container and vacuumized, and a phase change nanosphere suspension is added to impregnate the wet-spun fibers at 70° C. After impregnation for 3 hours, the fibers are washed and dried at room temperature at 25° C. to obtain phase change fibers.

[0050] The DSC curve of the phase change fiber obtained in Example 2 is shown in Figure 3 .

[0051] Embodiment 3:

[0052] (1) Weigh 60 g of polyethylene glycol, 0.8 g of styrene-maleic anhydride hydrolyzate, 15 g of polydimethylsiloxane, and 1.2 g of butyltin sulfate, dissolve them in water, and after ultrasonic dispersion for 10 min, place them in an oil bath and heat them to 50° C. for reaction for 1 h; start a high-speed stirrer, adjust the stirring rate to 5000 rpm, increase the reaction temperature to 80° C., and react for 6 h to obtain a mixed solution;

[0053] (2) After the mixed solution is taken out and cooled, it is placed in a freeze dryer, frozen for 20 minutes at a vacuum degree of 2 Pa and a temperature of -30°C, and dried for 8 hours to obtain phase change nanoparticles, and water is added to prepare a phase change nanoparticle suspension with a mass concentration of 20% for later use;

[0054] (3) dissolving cellulose in anhydrous ethanol to obtain a spinning solution with a concentration of 50 wt%, using pure water as a coagulation bath, wet spinning at room temperature, setting the flow rate to 1 m / min, and obtaining wet-spun fibers after curing for 30 min;

[0055] (4) The wet-spun fibers are subjected to vacuum treatment to remove the air and moisture contained therein, and then the treated wet-spun fibers are placed in an impregnation container and vacuumized, and a phase change nanosphere suspension is added to impregnate the wet-spun fibers at 80° C. After impregnation for 2.5 hours, the fibers are washed and dried at room temperature at 25° C. to obtain phase change fibers.

[0056] Comparative Example 1:

[0057] (1) Weigh 40 g of polyethylene glycol, 1 g of styrene-maleic anhydride hydrolyzate, 6 g of methyl methacrylate, and 1 g of dibutyltin dimaleate, dissolve them in water, and after ultrasonic dispersion for 10 min, place them in an oil bath and heat them to 50° C. for reaction for 1 h; start a high-speed stirrer, adjust the stirring rate to 5000 rpm, increase the reaction temperature to 80° C., and react for 6 h to obtain a mixed solution;

[0058] (2) After the mixed solution is taken out, it is washed and dried to obtain phase change nano-microspheres, and water is added to prepare a phase change nano-microsphere suspension with a mass concentration of 30% for later use;

[0059] (3) dissolving polyurethane in anhydrous ethanol to obtain a spinning solution with a concentration of 40 wt%, using pure water as a coagulation bath, wet spinning at room temperature, with a flow rate set at 1 m / min, and obtaining wet-spun fibers after curing for 30 min;

[0060] (4) The wet-spun fibers were immersed in a phase change nanosphere suspension at 50°C for 4 h, washed, and dried at room temperature of 25°C to obtain phase change fibers.

[0061] The DSC curve of the phase change fiber obtained in Comparative Example 1 is shown in Figure 4 .

[0062] The phase change properties of the phase change fibers obtained in Example 1, Example 2, Example 3 and Comparative Example 1 are shown in Table 1. As can be seen from Table 1, the enthalpy value of the phase change fiber obtained after vacuum treatment and then impregnation is higher, indicating that the phase change properties of the fiber are better reflected after vacuum treatment.

[0063] Table 1: Phase change properties of phase change fibers obtained in Example 1, Example 2, Example 3 and Comparative Example 1

[0064] sample Melting temperature Melting enthalpy Crystallization temperature Crystallization enthalpy Example 1 28.02℃ 12.237J / g 14.23℃ 11.902J / g Example 2 28.12℃ 11.121J / g 13.53℃ 10.253J / g Example 3 28.03℃ 11.546J / g 14.13℃ 10.766J / g Comparative Example 1 27.82℃ 9.286J / g 13.74℃ 8.878J / g

[0065] In the description of this specification, the description with reference to the terms "one embodiment / method", "some embodiments / methods", "example", "specific example" or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment / method or example are included in at least one embodiment / method or example of the present application. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment / method or example. Moreover, the specific features, structures, materials or characteristics described may be combined in a suitable manner in any one or more embodiments / methods or examples. In addition, those skilled in the art may combine and combine the different embodiments / methods or examples described in this specification and the features of the different embodiments / methods or examples, unless they are contradictory.

[0066] It should be noted that, in the present application, relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply that there is any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that the process, method, article or equipment including a series of elements includes not only those elements, but also includes other elements not explicitly listed, or also includes elements inherent to such process, method, article or equipment. In the absence of more restrictions, the elements defined by the sentence "comprise one..." do not exclude the existence of other identical elements in the process, method, article or equipment including the elements. In the present application, the meaning of "multiple" is at least two, such as two, three, etc., unless otherwise clearly and specifically stipulated.

[0067] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features applied for herein.

Claims

1. A method for preparing an interpenetrating network phase change fiber, characterized in that: The following steps are involved: S101, ultrasonically dispersing the phase change material, monomer, initiator and stabilizer, heating for reaction and stirring to obtain a mixed solution; S102, freeze-drying the mixed solution to obtain phase-change nano-microspheres, adding water to obtain a phase-change nano-microsphere suspension; the phase-change nano-microspheres are formed by irregular accumulation of small spheres with a particle size of 200 nm; S103, dissolving a wet spinning raw material in a solvent to obtain a spinning solution, and preparing a wet spinning fiber by a wet spinning process; S104, impregnating the wet-spun fiber in a phase change nano-microsphere suspension in a vacuum environment, and after the impregnation is completed, washing and drying to obtain an interpenetrating network phase change fiber; Among them, the phase change material is a mixture of any one or more of polyethylene glycol, paraffin, and high-density polyethylene; the monomer is any one of methyl methacrylate, styrene, and polydimethylsiloxane; the initiator is any one of styrene-maleic anhydride hydrolyzate, potassium persulfate, and dibenzoyl peroxide; the stabilizer is a mixture of any one or more of organic tin stabilizers, lead stabilizers, and rare earth stabilizers; the wet spinning raw material is a mixture of any one or more of polyurethane, chitosan, and cellulose.

2. The method for preparing the interpenetrating network phase change fiber according to claim 1, characterized in that: In step S101, the weight proportions of the raw materials are: 30-100 parts of phase change material, 0.2-1 parts of initiator, 0.5-2 parts of stabilizer, and 5-20 parts of monomer.

3. The method for preparing the interpenetrating network phase change fiber according to claim 1, characterized in that: In step S101, the heating temperature is 50-80°C, and the stirring speed is 3000-5000 rpm.

4. The method for preparing the interpenetrating network phase change fiber according to claim 1, characterized in that: In step S102, the freezing temperature of the freeze-drying is -20 to -200°C, the freezing time is 30 to 60 minutes, and the drying time is 6 to 12 hours.

5. The method for preparing the interpenetrating network phase change fiber according to claim 1, characterized in that: In step S103, the concentration of the spinning solution is 20-60 wt%, and the flow rate is 0.1-50 m / min.

6. The method for preparing the interpenetrating network phase change fiber according to claim 1, characterized in that: In step S104, the immersion temperature is 50-150° C., and the immersion time is 1-4 hours.

7. An interpenetrating network phase change fiber, characterized in that: The method is prepared by the preparation method according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Preparation method of composite phase change fiber

    CN116555937A

  • Photoinduced heating and temperature sensing elastic phase change energy storage fiber and preparation method thereof

    CN116590915A

  • Elastic phase change energy storage polyurethane fiber and preparation method thereof

    CN113235299A